Hubungan Beban Kerja dengan Tingkat Stres Kerja Perawat di Instalasi Rawat Inap Rumah Sakit Islam Malahayati Kota Medan - Luthfia Aina Salsabila Parinduri; Reni Agustina Harahap; Abdul Karim Batubara; Zuhrina Aidha (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Nurses are health professionals who face high workloads, both physically and mentally. Work-related stres within healthcare organizations is an important issue that needs attention due to increasing demands for efficiency and responsibility in providing care. This study aimed to examine the relationship between workload and work stres levels among nurses in the Inpatient Unit of Malahayati Islamic Hospital, Medan City. The study employed a quantitative approach with a cross-sectional design and involved 66 nurses selected using the cluster random sampling technique. The research instruments consisted of workload and work stres questionnaires, and the data were analyzed using the Chi-Square test with a significance level of 0.05. The results of the statistical analysis showed that there was a significant relationship between workload and work stres levels in nurses, with a p-value of 0.004 (p <0.05). However, the relationship was not always linear, as some nurses with low workloads experienced high stres, while high workloads were not always accompanied by high stres levels. The study concludes that there is a significant relationship between workload and nurses' work stres. It is recommended that hospitals conduct regular evaluations of nurses' workloads and encourage them to enhance time management and stres management skills through spiritual approach.